Description of the last stadium larva and female of Microgomphus thailandica Asahina, 1981 (Odonata: Gomphidae) - Boonsoong, Boonsatien; Chainthong, Damrong (Zootaxa, 2014)
The last stadium larva of Microgomphus thailandica is described, illustrated and compared with the larvae of congeneric species based on reared specimens collected from the Phachi headwater stream, Ratchaburi province, Thailand. The female adult of this species is described for the first time from a reared specimen from the same locality.